Beyond Charity: Study on Islamic Philanthropy Governance and the Implementation of Zakat Law - Abidin, Zaenal; Azman, Azlinda; Singh, Paramjit Singh Jamir (Legality : Jurnal Ilmiah Hukum, 2026)
This study focuses on the implementation of Zakat Law No. 23 of 2011 in Indonesia, particularly by the Lazismu Representative Office of East Java Province. Through an empirical legal approach, this study intends to evaluate the governance and compliance of the Lazismu Representative Office of East Java Province with the provisions of applicable laws, as well as its contribution to the SDGs based on community empowerment as a policy framework. This case study obtained data through interviews, observations, and data analysis to assess the compliance of the Lazismu Representative Office of East Java Province with relevant zakat regulations and the utilisation of zakat funds. This study has found a disparity between the explicit normative expectations of the Zakat Law No. 23 of 2011 and its implementation, particularly in the aspects of distributing zakat, infaq, and shodaqoh for community empowerment whose impact is sustainable. More than 70% of the programs implemented and initiated by Lazismu have been in line with the achievement of the SDGs, especially SDG 1 (No Poverty) and SDG 4 (Quality Education). However, this study also shows that 80% of the zakat, infaq, and shodaqoh of Lazismu utilisation programs remain charitable in nature but do not adequately promote participatory and inclusive community empowerment. As highlighted in this study, in the policy framework of the Zakat Law No. 23 of 2011 and its derivative regulations, there have not been many operational standards for the implementation of zakat utilisation guided by the principles of community empowerment with a participatory, accountable, and substantive governance approach in the management of zakat.